Use of georeferencing as a sustainable planning tool for aquaculture production in small municipalities: a case study for Ouro Verde do Oeste/PR (Research, Society and Development, 2023)
Small municipalities are important for regional socioeconomic development. The agricultural potential can be expanded when planned to use georeferencing tools that make it possible to generate maps, such as: land occupation, availability of natural resources, altimetry, among others. aiming at economic growth with environmental sustainability. This work aims to demonstrate the potential of using georeferencing to stimulate the sustainable economic growth of fish production in small municipalities. The municipality of Ouro Verde do Oeste was chosen to demonstrate the potential of geotechnology tools. Data from the IBGE – Brazilian Institute of Geography and Statistics, and geolocation tools such as QGIS were used to create maps of occupation and land use, quantification and classification of nurseries excavated in the municipality. The cost of implanting nurseries in places with high altimetry raises the costs of implanting projects. The maps generated through georeferencing tools, increasingly, become important for the correct planning of the production chain, both aquacultures, in the case of this study, and in other production chains.